Yield Components of Some Sesame Mutant Populations Induced by Gamma Irradiation - Vina Eka Aristya; Taryono Taryono; Rani Agustina Wulandari (Buletin Tanaman Tembakau, Serat & Minyak Industri, 2018)
Sesame is an producing seed whose oil is commercially needed. Breeding attempts to improve the productivity of sesame and yield components are induction of gamma ray irradiation mutations (Co-60). This study was aimed to identify effects of induced mutation by gamma rays irradiation in quantitative characteristics and yield of sesame in M4 generation originated from local cultivars. Two types of sesame (black and white) are irradiated with eight doses (100-800 Gy) of Co-60. The result showed a high variation in almost all morphological characters and modified the character of stem height from base to first branch, number of capsules per plant, biomass yield per plant, and seed yield per plant. Sesame irradiated with 600 Gy Co-60 doses has a beneficial effect on the number of capsules (black:120.23; white: 255.23, respectively) and the weight of 1000 seeds (black:3.63 g; white: 4.55 g, respectively). Genotypic Coefficient of Variation in M4 generation were recorded for high value for characters number of primary branches (30.16%), stem height from base to the first branch (30.96%), stem height from base to first capsule (14.82%), number of secondary branches (53.64%), number of nodes to first flower (72.66%), number of capsules/plant (44.90%), biomass yield/plant (28.37%), and seed yield/plant (36.68%). Genetic variability of plant population is very important for plant breeding program and to sustain level of high productivity.Komponen Hasil Beberapa Populasi Mutan Wijen yang Diinduksi oleh Iradiasi GammaWijen adalah tanaman penghasil biji yang minyaknya dibutuhkan secara komersial. Upaya pemuliaan untuk meningkatkan produktivitas wijen dan komponen hasil adalah dengan induksi mutasi iradiasi sinar gamma (Co-60). Penelitian ini bertujuan mengidentifikasi pengaruh induksi mutasi iradiasi sinar gamma pada karakter kuantitatif dan hasil pada generasi M4 wijen yang berasal dari kultivar lokal. Dua jenis wijen (hitam dan putih) diiradiasi dengan delapan dosis (100-800 Gy) Co-60. Sejumlah pengaruh mutasi wijen berhasil menunjukkan variasi yang tinggi pada hampir semua ciri morfologi dan memodifikasi karakter tinggi batang dari pangkal ke cabang pertama, jumlah kapsul/tanaman, hasil biomassa/tanaman dan hasil biji/tanaman. Wijen yang diiradiasi dengan dosis 600 Gy Co-60 memiliki efek menguntungkan pada jumlah kapsul (hitam:120,23; putih: 255,23) dan berat karakter 1000 biji (hitam:3,63 g; putih: 4,55 g). Koefisien Keragaman Genotipik pada generasi M4 dicatat nilai tertinggi pada karakter jumlah cabang primer (30,16%), tinggi batang dari pangkal ke cabang pertama (30,96%), tinggi batang ke kapsul pertama (14,82%), jumlah cabang sekunder (53,64%), jumlah ruas ke bunga pertama (72,66%), jumlah kapsul/tanaman (44,90%), hasil biomassa/tanaman (28,37%), dan hasil biji/tanaman (36,68%). Keragaman genetik dari populasi tanaman sangat penting untuk program pemuliaan tanaman dan mempertahankan produktivitas yang tinggi.